Attitudes of Forensic Cases Towards Violence Against Women and Affecting Factors - Kemalettin Acar; Ayşe Seydaoğulları Baltacı; Volkan Zeybek (Genel Tıp Dergisi, 2022)
Objective: This study aims to determine the attitudes of forensic cases who applied to Pamukkale University Faculty of Medicine Department of Forensic Medicine towards violence against women and to investigate the variables affecting those attitudes. Method: 152 participants in the research filled questionnaire consisting of 45 questions, the sociodemographic characteristics of the cases, the state of being subjected to violence, and the ISKEBE Violence against Women Attitude Scale. Result: When ISKEBE scale mean scores of participants were examined, total score and score of the subscale related to attitudes towards the identity were found to be higher in females. The total score and both subscales were found higher for participants who were single, those living in city center, and those whom both they and their spouse had an education level of high school or above. Those who did not have children were found higher total score and score of the subscale regarding the attitudes towards the body. Conclusion: Results obtained in our study, in which the attitudes of forensic cases who have experienced a traumatic process related to violence against women and affecting factors were examined, were generally similar to the studies evaluating other groups in the society. We are of the opinion that implementing education policies that are prepared taking into account the society gender roles, especially the sexist and patriarchal attitudes of men towards women, and that cover all segments of the society, would be important to change attitudes related to violence against women.